Identification of flood-prone areas by integrated remote sensing model - Mustaffa, A.A.; A.W. Rasib; M.I. Rosli; M.A.M. Razi; M.S. Adnan; L.W. Tan (International Association of Lowland Technology, 2015)
Flood is one of the main natural hazards that normally occurs every year in Malaysia. Flood causes inconveniences to human as well as life, property and financial losses. Floods cause a range of adverse impacts, including human injuries and fatalities, damages to crop, property, and public infrastructure. In this study, the identification of flood prone area has been done by integrated remote sensing images with the Soil Conservation System-Curve Number (SCS-CN). Johor Bahru city centre and Nusajaya of Iskandar Malaysia were selected as a study area since they are involved with the rapid development. A Landsat-5 image has been used in development of elevation model while the hydrological model was utilized to estimate the peak surface runoff. Based on the result, the flood prone areas for Skudai River and the Plentong River have been identified. The rapid changes in landuse has significantly has caused these area classified as high risk of flood areas. The development of this hazard map could be a used as a guideline in planning any development in this areas.